FREQUENCY OF LINGUAL NERVE INJURY IN MANDIBULAR THIRD MOLAR EXTRACTION: A COMPARISON OF TWO SURGICAL TECHNIQUES - Shad, Saima; Shah, Syed Majid Hussain; Alamgir, Alamgir; Abbasi, Masroor Manshad (Journal of Ayub Medical College Abbottabad, 2015)
Background: Surgical removal of impacted mandibular third molar is associated with a number of complications including postoperative bleeding, dry socket, postoperative infection, and injury to regional nerves. Lingual nerve damage is one of the main complications. To prevent this complication different techniques had been used. Lingual flap reflection is one of these procedures in which lingual soft tissue is reflected and retracted deliberately, the nerve is identified and is kept out of the surgical field. The objective of this study was to evaluate a surgical technique for third molar removal which is associated with minimum frequency of lingual nerve damage. Methods: A randomized controlled trial was performed. A total of 380 patients with impacted mandibular third molars were included in this study. Each patient was allotted randomly by blocked randomization to group A where procedure was performed by reflection and retraction of lingual flap in addition to buccal flap and group B where procedure was performed by retraction of buccal flap only. Results: Lingual nerve damage occurred in 8.94% in Group A in which lingual flap retraction was performed but damage was reversible. In group B, 2.63% lingual nerve damage was observed and nature of damage was permanent. The difference was statistically significant (p=0.008). Conclusions: Lingual flap retraction poses 3.4 times increased risk of lingual nerve damage during extraction of mandibular third molar when lingual flap is retracted but the nature of damage is reversible.